2022
DOI: 10.3389/fpubh.2022.929473
|View full text |Cite
|
Sign up to set email alerts
|

Food Promotion and Children's Health: Considering Best Practices for Teaching and Evaluating Media Literacy on Food Marketing

Abstract: Food marketing to children is ubiquitous and persuasive. It primarily promotes foods of poor nutritional quality, influences children's food preferences and habits, and is a factor in childhood obesity. Given that food marketing relentlessly targets children in traditional/digital media and the built environment, children need critical media literacy skills that build their understanding of food marketing's persuasive effects. However, little research connects media literacy with food marketing and health, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…In the digital environment, marketing media literacy aims to encourage individuals to develop the ability to use knowledge and skills to understand the purpose of advertisements that promote brands and products through media platforms, mobile apps, and electronic devices [ 71 ]. The evidence has shown that the first action to achieve marketing media literacy is to be aware of the marketing formats and media used [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the digital environment, marketing media literacy aims to encourage individuals to develop the ability to use knowledge and skills to understand the purpose of advertisements that promote brands and products through media platforms, mobile apps, and electronic devices [ 71 ]. The evidence has shown that the first action to achieve marketing media literacy is to be aware of the marketing formats and media used [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elliott e colaboradores 33 destacam que para haver práticas de alfabetização midiática sobre marketing de alimentos, o apoio dos pais e responsáveis torna-se relevante, dado que estes são encarregados pelas compras e preparações de alimentos, podendo dessa forma contribuir para promover um ambiente alimentar mais adequado para a criança.…”
Section: Desenvolvimento Das Atividades De Campounclassified
“…Além desse foco em EAN, os autores destacam que essas ações não suprem a importância de políticas governamentais que protejam as crianças das influências negativas do marketing de alimentos. 33 No Brasil, a Agência Nacional de Vigilância Sanitária (ANVISA) implementou um regulamento baseado nas recomendações da OMS, a RDC nº 24, de 2010 com novas regras para a publicidade e propaganda de alimentos, divulgando alertas sobre o consumo exagerado de sal, açúcar e gorduras, com o objetivo de reduzir o impacto do marketing infantil de alimentos. 34 Inclusive, é muito importante que pais e cuidadores sejam protagonistas na conscientização e fiscalização dessas políticas públicas.…”
Section: Desenvolvimento Das Atividades De Campounclassified
“…They emphasized the necessity for interventions to address the detrimental effects of media exposure on kids' health. Elliott et al (2022) highlighted the significance of media literacy programs in addressing health issues by talking about the relevance of media literacy in educating and analyzing food marketing to promote healthy habits among youngsters .As a result, the references offer insightful information about the health risks associated with children's use of electronic media, emphasizing the necessity of all-encompassing strategies to encourage positive media habits and lessen the detrimental effects of excessive media exposure on kids' development.…”
Section: Challenges With Children's Health Related To Using Electroni...mentioning
confidence: 99%